Hikayat Hang Tuah : analisis struktur & fungsi - Sutrisno, Sulastin, 1924-; Putra, Heddy Shri Ahimsa; Al Mudra, Mahyudin, 1958- (Yogyakarta : Balai Kajian dan Pengembangan Budaya Melayu, 2008)
Literary criticism on Hikayat Hang Tuah, a classical Malay literature.
Includes bibliographical references (page 397-404) and index.
Koleksi sumbangan : Prof. Dato Dr. Nik Hassan Shuhaimi Nik Abdul Rahman.
Keywords: Hikayat Hang Tuah; Hikayat Hang Tuah -- Criticism, interpretation, etc; Malay literature -- Criticism, interpretation, etc